Persimmon production in Spain - Badenes, María L.; Gil-Muñoz, Francisco; Blasco, Manuel (ISHS, 2022)
Persimmon species (Diospyros kaki) was introduced in the Mediterranean in the XVII century. Despite this late introduction, it was very well adapted to the Mediterranean Basin countries and developed different cultivars in Spain, Italy and Greece. In Spain, the species remained as isolated trees for family consumption and a few hectares were cultivated until the end of the XX century. This situation changed at the end of the 90s, in which the province of Valencia arose as an important region for persimmon production and Huelva a second production area. Valencia accounts for 90% of the Spanish production. The production in Valencia is based on the cultivar ‘Rojo Brillante’ while the production in Huelva is based on the cultivar ‘Triumph’. Both cultivars are PVA type and hence the astringency needs to be removed before marketing. Due to the high quality and productivity of the cultivar ‘Rojo Brillante’, in the last 20 years the Spanish production increased from a few tons not included in the statistics of the Ministry of Agriculture to 500,000 tons. Spain ranks now as the third producing country after China and Korea. The production is based on the cultivar ‘Rojo Brillante’. Increasing the number of varieties of PCNA type is being difficult by the lack of availability of compatible rootstocks adapted to the Mediterranean soils.